Contribution to "Deliverable 7: Activity 2. Project Dissemination and Visibility" - Eusebio, Ana (2016)
Report for Deliverable 7: Activity 2 of MEDOLICO Project - Mediterranean Cooperation in the Treatment and Valorisation of Olive Mill Wastewater, EU Programme ENPI-CBCMED I-B/2.1/090